The Cauchy Problem of the Porous Medium Equation with Absorption (Journal of Partial Differential Equations, 1994)
In this paper we study the existence of solution for the following Cauchy problem {u_t = &#916u^m - u^p u(x,0) = u_0(x) We show how the growth condition of initial trace is determined by the absorption.
Keywords: Existence of solution; Cauchy problem; porous media equation